Utveckling av gran, Douglasgran, bok och tall under skärm av hybridlärk - Magnusson, Per Olof (SLU/Southern Swedish Forest Research Centre, 2004)
"Development of Norway spruce, Douglas fir beech and Scots pine with a larch shelter wood" is a report written by Per-Olof Magnusson. The thesis is a compulsory part of forest engineer program at "Skogsmästarskolan", SLU, Skinnskatteberg, Sweden. The purpose of this report is to describe and evaluate an experiment with hybrid larch (Larix x eurolepis) as shelter wood, and different tree species growth and survival depending on the density of the shelter wood. The experiment is conducted by southern Swedish forest research centre, faculty of forestry, SLU in Alnarp. The hybrid larch ought to be an interesting alternative to birch (Betula sp.) as shelterwood on suitable sites in southern Sweden. It outgrows both grass and other vegetation quickly and is regarded to be a good shelter tree to shadow tolerant tree species as beech and spruce. The timber prices is approximately the same as for spruce, but straight, knot free wood can have same prizes as pine. About 2000 hybrid larches per ha were planted 1974. After four thinnings and one storm there's now standing 230 trees in the dense shelter and 145 in the sparse shelter. Below the shelters and on one open area spruce (Picea abies) were planted in 1990. Due to heavy gracing a fence was built spring 1993. Beech (Fagus sylvatica), douglas fir (Psedotsuga menziesii) and pine (Pinus sylvestris) and spruce were planted in the tree areas, a dense shelter, a sparse shelter and an open area adjacent to the shelters. Since these results is based on only one experiment no final conclusions can be made, but the results give a hint on how the different tree species react on the shelterwood density. As expected the growth of all the different tree species increase with lesser amount of shelter wood (Fig. 2-3). The pines bellow the shelter woods were all killed by insects or by a combination of competition from the shelter and insects, at an early stage. The survival lies between 72 and 97 % for all the tree species except for the Douglas-fir. The lowest survival for Douglas-fir was below the sparse shelter wood (36 %). Overall it looks like the mortality is greater below the sparse shelter wood but the most probable reason for this is that the fence on this location was broken in a couple of places and roe deer and elk has got in and graced. You could probably see more obvious trends of survival if the experiment had been placed in a more frost affected area. One could also speculate if the spruce and beech would have a greater mortality without the shelter wood since grass grew thick amongst the plants.